MIDWIFERY COMMUNICATION ETHICS IN INDONESIA - Wanti, Dida; Sulastri, Eti (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
Communication serves as a crucial determinant in the provision of health services by midwives, thus necessitating careful consideration of ethical standards in communication. This study aims to elucidate the communication ethics of midwives from the perspective of public space, intending to offer advantages and knowledge to the community, particularly to stakeholders invested in midwifery. This research employs a literature study methodology. From the standpoint of public space, the ethics of midwife communication can be defined as a method of interaction between midwives and clients aimed at articulating the objectives of health services through dialogue, thereby achieving mutual agreements that safeguard clients and adhere to the midwife code of ethics. The public space serves as a venue for clients and midwives to address any problems. In public spaces, birth attendants and clients can express thoughts or findings openly and honestly. Moral discourse in the public domain can encompass any topic, and once all sentiments have been articulated, it will culminate in a decision regarding the optimal health service.